Prevalence of intestinal parasites during pre- and post-COVID-19 pandemic at a tertiary care center in Lebanon - El Achkar, Hani; Ghandour, Lina; Farran, Sarah; Araj, George F (The Journal of Infection in Developing Countries, 2023)
Introduction: Intestinal parasitic infections (IPIs) are a major medical and public health problem, especially in developing countries. This study aimed at comparing the prevalence and types of IPI during pre- and post-COVID-19 pandemics, and with data reported in Lebanon a decade ago. Methodology: Stool specimen results from a total of 4,451 and 4,158 patients were examined using the concentration method during the pre-covid (2017-2018) and post-covid (2020-2021) pandemic periods, respectively. Demographic information related to patient’s age and gender was recorded. Results: The overall positive detected parasites among the total tested in these two periods were 589 (13.2%) and 310 (7.5%), respectively. The protozoa accounted for most parasites (e.g., Blastocystis hominis, Entamoeba coli (E. coli), Entamoeba histolytica, and Giardia lamblia). Only B. hominis and E. coli showed significant differences; B. hominis was more prevalent in the post-covid period (33.5%) whereas E. coli in the pre-covid phase (44.5%). Among gender, E. histolytica was higher in males during the post-covid period (13.3% vs. 6.3%). Regarding age, adults (between 26 and 55 years) had the highest prevalence, with a noticeable decrease among the elderly in the post-covid time. Compared to the previous decade, the prevalence of B. hominis and E. coli remained higher, and that of E. histolytica and G. lamblia was almost the same. Conclusions: These findings indicate an overall reduction in the prevalence of IPI during the post-covid period, though IPIs persistence remains high. This highlights the need for enhancing public health awareness efforts to improve hygiene and sanitation to reduce parasitic prevalence in Lebanon.